Tematy i rozwiązania funkcjonalne w twórczości warszawskiego architekta Juliana Ankiewicza
Fragm. pracy.
Iwona Szustakiewicz
Keywords: Ankiewicz, Julian (1820-1903); Architektura polska; historia; 19 w; Warszawa; budownictwo